Effectiveness of 0.1% Retinol Serum and Astaxanthin Gel on Skin Photoaging - Boedhy Setyanto; Sinta Murlistyarini; Dea Florensia (Fakultas Kedokteran Universitas Brawijaya, 2022)
Skin photoaging is cumulative skin damage due to chronic environmental exposure, especially ultraviolet (UV) light, which interferes with the keratinocyte and fibroblast syntheses by matrix metalloproteinases (MMP). Retinol can improve wrinkles, pigmentation, elasticity, firmness, brightness, and various signs of photoaging on the skin. Astaxanthin is a powerful antioxidant that protects the skin from UV rays, inhibits MMP, and stimulates collagen production. This case report presents 2 cases of women complaining about deep skin wrinkles, dullness, and looseness. Physical examination in the facial region revealed wrinkles when resting in the first patient and wrinkles during motion in the second patient. The first patient was diagnosed Glogau III photoaging, while the second patient was diagnosed Glogau II photoaging. Both patients received astaxanthin gel therapy and SPF 33 sunscreen cream every morning, as well as 0.1% retinol serum every night. There was an improvement after six weeks. Astaxanthin and retinol 0.1% can be used as photoaging therapy. Adequate use of photoprotection is also necessary to prevent the worsening of photoaging.